Facilities and accessibility in old folk’s home / Mohd Afiq Mohd Nazeri - Mohd Nazeri, Mohd Afiq (Universiti Teknologi MARA, Perak : Seri Iskandar: Faculty of Architecture, Planning & Surveying, 2009)
The preparation of this dissertation was mainly motivated by the desire to provide an overview of facilities and accessibility in old folk’s home in private practice especially at Klang Valley. These are intended to establish the good practice of Malaysian Standard to be adopted in the facility management of old folk’s home. The study has specific aim and objectives to achieve in the end. The primary aim of this study is to highlight guideline and standard of facilities and accessibilities for old folk in old folk’s home in Malaysia. Second objective is to identify whether standard facilities and accessibilities for old folk at private old folk’s home are applied or not and the third is to propose recommendation for better living environment in old folk’s home. This dissertation includes the outlines of the introduction to the subjects and each sub topic, and also explained elaborate about the old folk’s homes and responsible body in Malaysia, statistic old folk’s home and also standard facilities and accessibility in Malaysia. Research methodology which had been applied in the three (3) case studies are through observations, inspection to element and interviewing relates person of the three old folk’s homes. Then analysis and comparison between case studies due to guideline Malaysian Standard (MS 1184,2002). Form analysis it can be find that the best application of Malaysian Standard (MS 1184,2002) to accessibility and facilities is Golden Age Nursing Home, follow by Bluebell Homecare and then Sentosa Nursing Home. It is affected by type of property, owner sensitivity, financial and knowledge about requirement old folk’s home. Finally, conclusion from the research findings and development of recommendations for future improvement of old folk’s homes.